Model Penelitian Hubungan Ilmu dan Agama dalam Pendidikan Agama Islam - Jaswan Jaswan; Tobroni Tobroni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study explores the integration of knowledge and religion within Islamic education, focusing on the development of models that connect both domains. Utilizing a qualitative-descriptive approach, the research analyzes various integration models, including the justification of knowledge through Quranic verses, collaboration between science and religion, and the reconstruction of knowledge within Islam. The findings indicate that the integration of knowledge and religion not only enhances students' academic understanding but also shapes their character and morals in alignment with Islamic values. The study also identifies challenges faced in implementing integration models and provides recommendations for developing a more comprehensive curriculum. Thus, this research contributes to the understanding of the significance of integrating knowledge and religion in fostering an educated and ethical generation.